2022
DOI: 10.4103/ijo.ijo_3216_21
|View full text |Cite
|
Sign up to set email alerts
|

Association of keratoconus with serum levels of 25-hydroxyvitamin D and antioxidant trace elements: A systematic review and meta-analysis

Abstract: The aim of this systematic review and meta-analysis was to summarize and compare the available evidence on the level of vitamin D and antioxidant trace elements between the keratoconus (KC) patients and healthy controls. Seven case–control studies with 830 subjects were found eligible with a systematic search using PubMed, SCOPUS, Web of Science, and EMBASE till November 21, 2021. Data were synthesized with a DerSimonian and Laird random-effects method of meta-analysis. The mean serum vitamin D level was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The meta-analysis by Gupta PC suggested that a low level of vitamin D can be associated with higher odds of severe keratoconus. Thus, routine monitoring of vitamin D levels and trace elements in KC patients at the time of diagnosis and during subsequent follow-up appointments could serve as a predictive measure for assessing disease severity [ 25 ].…”
Section: Keratoconus (Kc)mentioning
confidence: 99%
“…The meta-analysis by Gupta PC suggested that a low level of vitamin D can be associated with higher odds of severe keratoconus. Thus, routine monitoring of vitamin D levels and trace elements in KC patients at the time of diagnosis and during subsequent follow-up appointments could serve as a predictive measure for assessing disease severity [ 25 ].…”
Section: Keratoconus (Kc)mentioning
confidence: 99%
“…It can affect structural changes, such as stromal corneal haze and a topographical relative inferior teardrop steepening pattern, such as found in KC. Decreased Vitamin D serum levels have been associated with KC development and severity [35,36]. Similarly, elevated immunoglobulin E (IgE) levels are correlated to CE severity [37].…”
Section: Bloodmentioning
confidence: 99%
“…Patients with keratoconus, particularly those with progressive disease, are shown to have lower serum levels of vitamin D than the normal population. [ 61 - 63 ] Our group has shown decreased expression of VDR in epithelium over the ectatic zones of cornea in keratoconus. [ 64 ] We further demonstrated that vitamin D addition helps induce VDR in epithelial cells under oxidative stress.…”
Section: Vitamin D and Keratoconusmentioning
confidence: 99%